Ķazaķstan – žaṇa sipattaġy zajyrly el = Kazakhstan – the secular state of a new form = Kazachstan – svetskoe gosudarstvo novoj formy - Dosay, Kenzhetay (Chabaršy. Dintanu serijasy, 2015)
This article comprehensively addressed questions of history of interaction between religion and politics in Kazakhstan. The author in a study of this problem especially paid attention to the complex and contradictory process of interaction of Islam and the state in the history of the Kazakhs